2021
DOI: 10.3390/ijerph182413222
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Body Dissatisfaction in Adolescents: The Moderating Role of Thin- and Muscular-Ideal Internalisation

Abstract: Internalisation of appearance ideals moderates the relationship between exposure to media images and body dissatisfaction. To date, the role of thin- and muscular-ideal internalisation in the context of social media remains under explored, particularly for boys. As such, we aimed to explore how social media use (Instagram and Snapchat) was related to body dissatisfaction, and whether thin- and muscular-ideal internalisation would moderate this relationship in a sample of 1153 adolescent boys and girls (55.42% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 91 publications
1
26
0
5
Order By: Relevance
“…The same was observed in the correlation between IA and BIC; correlations were significant, positive, and moderate for both the total sample and the various groups, with the only exception again being late adolescence (r = 0.190, p = 0.274). These results are in line with previous studies indicating that excessive use of social media can have a negative impact on body image [ 27 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…The same was observed in the correlation between IA and BIC; correlations were significant, positive, and moderate for both the total sample and the various groups, with the only exception again being late adolescence (r = 0.190, p = 0.274). These results are in line with previous studies indicating that excessive use of social media can have a negative impact on body image [ 27 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Especially the mass media can lead adolescents to internalize Western society’s ideals of physical attractiveness and beauty, leading to body dissatisfaction when these standards are perceived as not being met [ 7 , 8 ]. Recent findings have also shown that greater use of social media (Instagram and Snapchat) is associated with higher body dissatisfaction [ 9 ]. In accordance with sociocultural models of the development of body dissatisfaction and eating disorders [ 10 ], pressures on appearance from peers, family, and the media, and psychological processes participate in the onset and persistence of body dissatisfaction: internalization and pressures to conform to these socially prescribed body ideals explain the associations between weight status and BI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dual pathway model suggests sociocultural appearance pressures and the internalization of appearance ideals lead to body dissatisfaction and subsequent risk factors for eating disorder development such as disordered eating behaviors [ 68 ]. Pressure to conform to appearance ideals through adolescent girls’ social media use and the extent to which they internalize these ideals may contribute to body dissatisfaction [ 9 ] and consequently, their likelihood of engaging in disordered eating behaviors with impacts on their mental health [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Time spent on the Internet has been associated with increased body dissatisfaction among adolescent girls, with the interaction allowed by social media and appearance-focused content influencing body image concerns through negative social comparisons and peer normative processes [ 11 , 19 22 ]. Images of attractive thin females, often photo-shopped with filters, feature frequently on social media platforms such as Instagram, promoting stereotyped beauty ideals subsequently affecting viewers’ body image and dissatisfaction [ 9 , 23 ]. The females in images on social media are more commonly peers rather than celebrities like those included in mass media, which may influence body image related attitudes and concerns more significantly, given peers’ relatability and relevance to girls’ daily lives [ 19 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%